Mo‐Doped Cobalt Phosphide Nanosheets for Efficient Hydrogen Generation in an Alkaline Media. Issue 6 (26th April 2019) - Liu, Xunhang; Wei, Bo; Su, Ren; Zhao, Chenguang; Dai, Dongmei; Ma, Xiao; Xu, Lingling
Abstract : The development of high‐active, low‐cost, and robust electrocatalysts is vitally important for electrocatalytic water splitting. Herein, Mo‐doped cobalt phosphide (Mo‐CoP) nanosheets on carbon cloth are successfully prepared and evaluated for hydrogen evolution reaction (HER) catalyst. The Mo‐CoP catalyst displays an excellent electrocatalytic activity and stability toward HER in 1 m KOH solution. Relatively low overpotentials of 49 and 120 mV are required to reach the current densities of 10 and 100 mA cm −2, respectively. Moreover, the Mo‐CoP catalyst shows an exceptional stability with 24 h operation. The origin of improvement can be ascribed to Mo doping, which probably results in more active sites, higher electrical conductivity, and faster mass transfer. This work demonstrates a promising electrocatalyst for water electrolysis in an alkaline media and opens new possibilities for exploring water‐splitting catalysts. Abstract : The introduction of Mo ion in cobalt phosphide foam nanosheet microstructure greatly promotes hydrogen evolution activity in 1 m KOH media. Moreover, the catalyst displays an excellent electrocatalytic stability.